The effects of palm kernel cake utilization in rattion on the body composition of broiler - Dady S. N.; Romziah S. B. (Hemera Zoa, 1992)
The experiment was conducted to study the effects of ration containing 0, 25, 50 and 75% of palm kernel cake (PKC) on the body compositiion of broiler.Results of the experiment showed that ration containing PKC ut to 50% given to the broilers did not have significant influence (p>0.05) on carcas weight. Carcas weight decreased (p < 0.05) when ration containing 75% PKC. Weight of meat and bone decreased (P